An Apical Meristem-Targeted in planta Transformation Method for the Development of Transgenics in Flax (Linum usitatissimum): Optimization and Validation - Kesiraju, Karthik; Tyagi, Shaily; Mukherjee, Soumyadeep; Rai, Rhitu; Singh, Nagendra K.; Sreevathsa, Rohini; Dash, Prasanta K. (Frontiers in Plant Science, 2021)
Efficient regeneration of explants devoid of intrinsic somaclonal variations is a cardinal step in plant tissue culture and thus a vital component of transgenic development technology. However, recalcitrance of economically important crops to tissue culture based organogenesis ensues a setback in the use of transgenesis in genetic engineering of crop plants. The present study developed an optimized, genotype independent, non-conventional, tissue culture independent in planta strategy for transformation of flax/linseed. This apical meristem-targeted in planta transformation protocol will accelerate value addition in the dual purpose industrially important but recalcitrant fibre crop flax/linseed. The study delineates optimization of Agrobacterium tumefaciens mediated transformation and stable T-DNA (pCambia2301:GUS:nptII) integration in flax. The study established the successful use of a stringent soilrite-based screening in the presence of 30 ppm kanamycin for the identification of putative transformants. The amenability, authenticity and reproducibility of soilrite-based kanamycin screening was further verified at molecular level by GUS histochemical analysis of T0 seedlings; GUS and nptII gene specific PCR and genomic Southern hybridization for stable integration of T-DNA. This method resulted in 6.05% screening efficiency in presence of kanamycin indicating amenability of in planta flax transformation. The in planta transformation strategy can be a promising tool for the successful development of transgenics in flax.